Some Specific Features of the Object of Prosecutorial Supervision over the Observance of Constitutional Rights of the Individual to Work - Tishkov, Daniil S. (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
The article defines the place of supervision functions within the system of the functions of prosecution bodies of the Russian Federation as one of the priority sectors of prosecutorial supervision. The legal regulation of prosecutorial supervision of the rights and freedoms of Russian Federation citizens is examined. The Author reveals the specific features of the subject of prosecutorial supervision in compliance with the constitutional rights of the individual to work based on the results of the current legislation system analysis. The assumption of the need for changes to the Prosecutor General of the Russian Federation organizational and administrative documents in order to increase the efficiency of prosecutorial supervision over the observance of individual’s constitutional rights to work is expressed.